Development of Warehouse Management System Using IoT for Halal Supply Chain - Muhammad Rizki; Hilman Zarory; Afif Naufal Luthfi (International Journal of Science and Society, 2023)
This research aims to develop a Warehouse Management System (WMS) using Internet of Things (IoT) technology to support the implementation of the Halal Supply Chain. Given the importance of monitoring and guaranteeing halal products in the supply chain, IoT in warehouse management systems can provide greater transparency, efficiency, and accuracy. This study introduces an IoT-based WMS model that enables real-time tracking from goods receipt to delivery and automates processes such as selecting storage locations and picking up goods. In addition, this system is also designed to ensure compliance with halal standards by tracking the source of raw materials and monitoring their storage conditions. System testing showed significant improvements in warehouse operational efficiency and the ability to guarantee the integrity of halal products. These results indicate that adopting an IoT-based WMS can be essential to realizing an influential and trustworthy Halal Supply Chain.